ANALISIS PENGARUH PENDAPATAN NASIONAL DAN TINGKAT SUKU BUNGA TERHADAP PENGHIMPUNAN DANA PIHAK KETIGA PADA BANK UMUM DI INDONESIA - Soelistyo, Aries; Arrohmah, Khoirunnisa’ (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2010)
The principal problem of this study are associated with the Indonesian economy which needs to be improved, therefore Government could increase through improved and increased banks' performance by increasing the national income, where the banking, especially commercial banks at the core of the financial system of State. The method used in this study is multiple linear regression partial adjustment model (Partial Adjustement Model) that is useful to observe the response of short-term and long-term variable from one unit change in the value of independent variables. From the analysis results obtained equation is LSt = β0 + β1LYt + β2 Lrt + β3 LSt-1 + μt. The results showed that the model free from the classical assumption of multicollinearity, heteroscedasticity, autocorrelation. As for all significant independent variables simultaneously on the third party funding variables, this suggests that the third party funding increase is influenced by many factors could be shown the results of the regression is calculated for 679.8788 F <F table at 2.48. And partially variable interest rate not significantly affect the third party funding.